Motivasi Orang Pergi Haji Berulang Kali: Analisis tentang Pengalaman dan Kesadaran Beragama sebagai Budaya Islam di Yogyakarta, Indonesia - Jailani, Mohammad; Huda, Miftachul (Pascasarjana UIN ANTASARI Banjarmasin, 2024)
The issues that arise regarding the Hajj include those who wait in line for years without being called by the Ministry of Religious Affairs. There is also a strong motivation for some to perform the Hajj multiple times. The research problem consists of two variables: first, why do people go on Hajj repeatedly; second, is it true that the religious experience during Hajj is a factor in the desire to perform Hajj again? This study aims to analyze the motivation of people to perform Hajj repeatedly in the holy land from the perspective of religious psychology (religious consciousness). The method used in this study is qualitative, a field study with interview and documentation methods. The respondents in this study are all pilgrims who have performed Hajj at least twice and reside in Yogyakarta and its surroundings. The results of this study prove that there is an influence of understanding regarding the legal conclusions on religious orders about performing Hajj. It is believed that performing Hajj once in a lifetime is obligatory, while performing it multiple times is considered sunnah and therefore unlimited. Secondly, the religious experiences encountered during the Hajj rituals in the holy land of Mecca. These personal and spiritual religious experiences vary among pilgrims. The differences are due to the place, time, atmosphere, health conditions of the pilgrims, and the quality of understanding of religious teachings. Among the religious experiences that tend to raise religious awareness can take the form of specificity, emotion, amazement, and also helplessness, leading to self-introspection, which further impacts the growth of personal and social holiness. Lastly, the task given by an institution or another person is believed to be a call from Allah, as not everyone gets the opportunity to perform Hajj. The Hajj culture in Indonesia is not just a tradition or ritual but an enhancement of Islamic culture that has implications for Islamic culture. It is known that 80-100% of Indonesians are motivated to perform Hajj.